Gender Differences in Meaningful Leisure Among Older Adults: Joint Displays of Four Phenomena - Jaumot-Pascual, Nuria; Monteagudo, María Jesús; Kleiber, Douglas A.; Cuenca, Jaime (Frontiers in Psychology, 2018)
Vital events, such as widowhood and retirement, are broadly accepted as points of inflection in the lives of older adults that often differ according to gender. In this study, we analyzed the influence of gender on meaningful leisure among older adults through the integration of qualitative and quantitative findings. The use of joint displays revealed that in this sample of people from Northern Spain: (1) there were no significant differences in the influence of retirement and widowhood on the leisure of the two genders, (2) the ethic of care was a constraining factor in older women’s leisure, (3) women were more innovative in their leisure in older age, and (4) volunteer activities were highly segregated by gender. The use of joint displays helped illuminate these four phenomena in light of quantitative and qualitative data.